Classroom management : models, applications, and cases - Manning, M. Lee; Bucher, Katherine Toth , 1947- (Pearson, 2013)
In Classroom Management; Models, Applications, and Cases, Third Edition, pre-service teachers and administrators are given a wealth of information and activities that will prepare them to develop and apply a personal classroom management philosophy. Using a models approach, Manning and Bucher present a thorough discussion of the theories, models, and philosophies of classroom management; tackle the growing problems of school violence and bullying(including the "safe school" movement and cyber-bullying); and give thoughtful discussion to diversity and classroom management. Accessible and practical, this book will help guide educators toward developing and applying a personal classroom management philosophy all their own that can be applied immediately in the classroom